Kinematics Modeling and Analysis of a Quadruped Bionic Horse Robot Driven by a Cam-link Mechanism - Xu Yang; Ruolan Wang; Liangwen Wang; Liwei Li; Tuanhui Wang (Jixie chuandong, 2021)
A quadruped walking robot with a bionic horse configuration for equestrian-assisted treatment is presented. A single leg system of the robot is driven by a cam-linkage combination mechanism. On the basis of introducing the structure and working principle of the quadruped bionic horse robot， the kinematics modeling and analysis of the robot are carried out. The kinematics equations of each mechanism are established by loop vector method， and Newton iteration method is used to solve the nonlinear displacement equations. The Matlab is used to develop a unified program to solve the displacement， velocity and acceleration of the moving leg of the robot. By an example， the characteristics of the endpoint displacement and acceleration of the moving leg for the robot driven at the same speed are analyzed. The relevant research lays a foundation for the subsequent optimizing the performance of the robot.